Ecotoxicological effects of the insecticide fipronil in Brazilian native stingless bees Melipona scutellaris (Apidae: Meliponini). (September 2018) - de Morais, Cássio Resende; Travençolo, Bruno Augusto Nassif; Carvalho, Stephan Malfitano; Beletti, Marcelo Emílio; Vieira Santos, Vanessa Santana; Campos, Carlos Fernando; de Campos Júnior, Edimar Olegário; Pereira, Boscolli Barbosa; Carvalho Naves, Maria Paula; de Rezende, Alexandre Azenha Alves; Spanó, Mário Antônio; Vieira, Carlos Ueira; et al.
Abstract: Melipona scutellaris Latreille, 1811 (Hymenoptera, Apidae) is a pollinator of various native and cultivated plants. Because of the expansion of agriculture and the need to ensure pest control, the use of insecticides such as fipronil (FP) has increased. This study aimed to evaluate the effects of sublethal doses of FP insecticide on M. scutellaris at different time intervals (6, 12, and 24 h) after exposure, via individually analyzed behavioral biomarkers (locomotor activity, behavioral change) as well as the effect of FP on different brain structures of bees (mushroom bodies, antennal cells, and optic cells), using sub-individual cell biomarkers (heterochromatin dispersion, total nuclear and heterochromatic volume). Forager bees were collected when they were returning to the nest and were exposed to three different concentrations of FP (0.40, 0.040, and 0.0040 ng a.i/bee) by topical application. The results revealed a reduction in the mean velocity, lethargy, motor difficulty, paralysis, and hyperexcitation in all groups of bees treated with FP. A modification of the heterochromatic dispersion pattern and changes in the total volume of the nucleus and heterochromatin were also observed in the mushroom bodies (6, 12, and 24 h of exposure) and antennal lobes (6 and 12 h) of bees exposed to 0.0040 ng a.i/bee (LD50/100 ). FP is toxic to M. scutellaris and impairs the essential functions required for the foraging activity. Graphical abstract: Image Highlights: Effects of fipronil on the foraging activity of M. scutellaris were evaluated. Sublethal doses of fipronil alter the average climbing speed of forager bees. Behavioral changes were generated in M. scutellaris contaminated with fipronil. Topical exposure to fipronil causes changes in heterochromatin . Fipronil is highly toxic and may be associated with the decline of bees in the world.